Pengembangan Modul Praktikum Teknik Pengolahan Menggunakan Media Penghantar Panas Di Smkn 2 Indramayu - Nopiyani, Julaeha (2014)
Tujuanpenelitianiniadalahmengembangkanmodulpraktikumpembelajaranteknologipengolahanmenggunakan media penghantarpanas, dasardaripengembangantersebutkarena di SMKN 2 Indramayutidakterdapatmoduluntukpegangan yang dapatmeningkatkanpemahamansiswa.Hal tersebutterlihatdarihasilbelajarsiswadikelassebelumnyapadakompetensisangatrendah.Makatujuanselanjutnyadalahmengetahuipeningkatanpemahamansiswa, dalam proses pembelajaranmenerapkanteknikpengolahanmenggunakan media penghantarpanas. Metodepadapenelitianinimenggunakanpenelitiandanpengembangan (R&D), dengananalisis data menggunakananalisishasilangketdandistribusifrekuensi.Hasildaripenelitianiniadalahmengetahuilangkahdalammengembangkanmodulpraktikumpembelajaranteknologipengolahanmenggunakan media penghantarpanasyaknimemvalidasidesainpadapakarahli, dilakukanperbaikanproduksesuaidengan saran yang diberikandariahli media berupakompenen yang diperbaikidanpenempatankomponentersebut, dariahlimaterimengenaikelengkapanmateri yang terdapatdalammodul, selanjutnyadilakukanpengujianpadakelaskecildenganresponden 10 orang siswa, selanjutnya yang dilakukanadalahmenerapkan. Pemahamansiswameningkatdimana 26 siswadari 27 orang siswamendapatkannilai yang melebihi KKM yakni 60. katakunci: pengembangan, modulpraktikum, teknikpengolahan Research purposes this is developing module lab work learning technology processing using media of carriage heat, the basis of the development was because in SMKN 2 Indramayu not contained module to grip that can promote understanding students.It seen the result learning students dikelas earlier on competence very low.So the purpose next was increased know understanding students, a learning process in applying technique processing using media of carriage heat.Methods to research is using research and development (R &D), with analysis of data using analysis result poll and distribution frequency.The result of this research is knowing step in developing module lab work learning technology processing using media of carriage heat namely validating design on experts, to the repair products in accordance with advice given of media experts in form of component repaired and the placement of the component, of expert material regarding the completeness of the material that has been found in the module, then conducted testing on small classes with 10 students, the respondents subsequently performed is implementation. Increased student understanding where 26 students from 27 student get value that exceeds the KKM of 60.